Networked Surfaces: A New Concept In Mobile Networking - Scott, James; Hoffmann, Frank; Addlesee, Mike; Mapp, Glenford; Hopper, Andy (Proceedings of the Third IEEE Workshop on Mobile Computing Systems and Applications (WMSA 2000), 2000)
Networked Surfaces are surfaces which provide network connectivity to specially augmented objects, when these objects are physically placed on top of the surface. When an object (e.g. a notebook computer) connects, a handshaking protocol assigns functions such as data or power transmission to the various conducting paths that are established. This paper describes the position occupied by this concept in the world of networking, presents an overview of the technology used in its realisation, describes the current prototype implementation, and outlines the potential implications of its introduction.